(untitled) (Pashupati Pragya पशुपति प्रज्ञा, 2026)
This paper examines a case of democratic backsliding in South Asia beyond Western-centric models. The focus is on assessing how past legacies, political culture and economic circumstances influence democracy in this part of the world. The paper takes a qualitative, comparative perspective and draws. Key findings indicate that the constitutionalizing and anchoring of democracy in constitutions and electoral systems are compromised by low institutional capacity, few social precursors to democracy, and increased authoritarianism. The resilience of civil society, the activism of women, and the presidency of young people are powerful forces working against it: they provide ample room to resist authoritarianism and generate space for local action. The paper highlights the contested and resurgent features of democracy and offers important lessons for scholars and policy makers.